Continuity conditions for the Hilbert transform on quasi-Hilbert spaces - Šahović, A.; Vajzović, F.; Peco, S. (Sarajevo Journal of Mathematics, 2024)
We give necessary and sufficient conditions for the continuity of the Hilbert transform on complex quasi-Hilbert spaces, i.e. on complex, reflexive, strictly convex Banach spaces with Gâteaux-differentiable norm and with generalized inner product.